GENETIC VARIABILITY AND CORRELATIONS IN FRENCH BEAN FOR YIELD IMPROVEMENT - SAVITA; D. K. SINGH; AJAY TOMER (The Bioscan, 2018)
The field experiment was carried out to estimate the extent of genetic variability and correlation between yield related traits to be used in breeding. Forty genotypes were used for the traits: plant height at 30 days after sowing of FB-118, FB-119 (8.51cm), days to FB-121, FB-123, FB-124, FB-125 50% flowering, highest leaf length (9.6 cm), leaf width (8.49cm), pod length (12.94cm), pod width (10.04mm), number of marketable pods per plant (9.31), pod yield per plant (65.82g), number of pods per plant (9.31), pod weight (5.83g), days to 50% maturity (66.27), seed length (17.18mm), seed width (8.22mm), number of seed per pod (49.86), green pod yield (131.70 Mt·ha-1), and 100 seed weight (49.86g) compared to Arka Komal, Arka Suvidha, Arka Anoop. Genetic analysis was used to estimate correlations of yield and related characters between French bean genotypes. Significant differences occurred for all characters studied. Green pod yield varied from 34.86 (‘FB-125’) to 133.26 Mt·ha-1 (‘FB-132’). Green pod yield exhibited a highly significant, positive, correlation with number of marketable pods per plant, pod yield per plant, and number of pods per plant, and was negatively correlated with days to 50% flowering. There was genetic variability for all traits among genotypes.